Interleukin‐33 requires CMRF35‐like molecule‐1 expression for induction of myeloid cell activation. Issue 6 (15th April 2014) - Shik, D.; Moshkovits, I.; Karo‐Atar, D.; Reichman, H.; Munitz, A.
Abstract Background IL‐33 is a potent activator of various cells involved in allergic inflammation, including eosinophils and mast cells. Despite its critical role in Th2 disease settings, endogenous molecular mechanisms that may regulate IL‐33‐induced responses remain to be defined. We have recently shown that eosinophils express CMRF35‐like molecule (CLM)‐1. Yet, the role of CLM‐1 in regulating eosinophil functions is still elusive. Methods CLM‐1 and CLM‐8 expression and cellular localization were assessed in murine bone marrow‐derived and/or peritoneal cells at baseline and following IL‐33 stimulation (flow cytometry, western blot). IL‐33‐induced mediator release and signaling were assessed in wild‐type (wt) and Clm1−/− cells and mice. Results BM‐derived eosinophils express high levels of glycosylated CLM‐1. IL‐33 induced a rapid, specific, concentration‐ and time‐dependent upregulation of CLM‐1 in eosinophils (in vitro and in vivo). Clm1−/− eosinophils secreted less IL‐33‐induced mediators than wt eosinophils. CLM‐1 co‐localized to ST2 following IL‐33 stimulation and was required for IL‐33‐induced NFκB and p38 phosphorylation. Th2 cytokine (e.g., IL‐5, IL‐13) and chemokine (e.g., eotaxins, CCL2) secretion was markedly attenuated in IL‐33‐treated Clm1−/− mice. Subsequently, IL‐33‐challenged mice displayed reduced infiltration of mast cells, macrophages, neutrophils, and B cells. Despite the markedly impaired IL‐33‐induced eotaxin expression in Clm1−/− mice, eosinophil accumulation was similar in wt and Clm1−/− mice, due to hyperchemotactic responses of Clm1−/− eosinophils. Conclusions CLM‐1 is a novel regulator of IL‐33‐induced eosinophil activation. These data contribute to the understanding of endogenous molecular mechanisms regulating IL‐33‐induced responses and may ultimately lead to receptor‐based tools for future therapeutic intervention in IL‐33‐associated diseases.